Application of carboxylate protic ionic liquids in simultaneous microalgal pretreatment and lipid recovery from marine Nannochloropsis sp. and Chlorella sp. (April 2019) - Shankar, Mukund; Chhotaray, Pratap K.; Gardas, Ramesh L.; Tamilarasan, Krishnamurthi; Rajesh, Mathur
Abstract: Protic Ionic Liquids (PILs) with their labile protons are expected to simultaneously disrupt and exudate lipids from microalgae, crucial for efficient biodiesel production. A survey study with a battery of ten carboxylate PILs with lactam and ammonium cations was conducted with dried and dewatered marine Nannochloropsis oculata and Chlorella salina microalgae. The results showed that the formate and hexanoate PILs in comparison to acetate PILs could efficiently catalyse simultaneous near-complete cell disruption and lipid extraction from dewatered microalgae. The ability of PIL to handle dewatered microalgae avoids the energy-intensive drying step used in other conventional methods. The maximum lipid recovery of 134.9 and 85.4‰ was recorded with butyrolactam hexanoate treated N. oculata and C. salina respectively. The lipid profile showed the predominant presence of C16 and C18 fatty acids and comparable with lipid profile obtained with conventional Bligh & Dyer method. The PILs were also found to favourably inhibit lipases which likely promote lipolysis in wet microalgal lipid samples. The PIL extracted lipids were found to have reduced pigments, favoured for reducing the number lipid/biodiesel purification steps. Highlights: Marine N. oculata and C. salina microalgae were processed for lipid recovery with ten different carboxylate-PILs. PILs exhibited enhanced lipid recoveries from dewatered microalgae than dried microalgae. Hexanoate and formate PILs exhibited enhanced lipid recovery compared to acetate PILs. The PILs exhibited varying degrees of lipase inhibition and recovered less-pigmented lipids.